Fast Method Of Image File Compression In Web-Based Application Form Using Huffman Algorithm - Ronny Saputra; Yuza Reswan; Yulia Darmi; Khairullah Khairullah (Penerbit Jurnal Indonesia, 2023)
Many web-based applications/forms serve as online data entry devices equipped with facilities for uploading image data. When uploading image data, the image file is often incompatible or cannot be uploaded because the size is too large. Users have to resize those files separately. For example, with several compression applications used such as photoshop, gimp, photoscape, photo compressor, image size and many other compression applications. Web-based applications should be able to automatically resize the file according to the appropriate file size so that it can save time and speed up the process. To deal with the problem of automatic compression, the user must provide or build a web-based application that can directly compress files on the web because automatic file or image compression is available on the website without compressing them separately beforehand. With this automatic compression form application, it certainly reduces costs. (quota) internet, shortening time and also making it easier for users or users when uploading files on the web. The algorithm that is suitable for resizing files in online web applications is the hufman algorithm.